Taxonomy of Venezuelan water beetles in the genus Hydrochus Leach, 1817, and an analysis of male genitalia morphology (Coleoptera: Hydrochidae) - Perkins, Philip D. (Zootaxa, 2019)
The taxonomy of Venezuelan water beetles in the genus Hydrochus Leach, 1817 is presented. The known fauna now consists of 26 species, 17 of which are described as new species. All species are described, or redescribed, diagnosed, and high-resolution images of the habitus and male genitalia of each species are given. The morphology and mechanics of the male genitalia of Hydrochus are described and illustrated, and a system of naming male genitalia characters in Hydrochidae is provided. The following new species are described: H. argutissimus n. sp., H. basilaris n. sp., H. bicarinatus n. sp., H. bituberculatus n. sp., H. collaris n. sp., H. conjunctus n. sp., H. denarius n. sp., H. formosus n. sp., H. hellmani n. sp., H. kellymilleri n. sp., H. leei n. sp., H. lobatus n. sp., H. mauriciogarciai n. sp., H. pictus new species, H. sagittarius n. sp., H. shorti n. sp., H. variabiloides n. sp. Hydrochus pseudosecretus Oliva 1996 is removed from synonymy with H. purpureus Knisch, H. soekhnandanae Makhan 1992 is removed from synonymy with H. pupillus Orchymont, and H. ramcharani Makhan 1992 is removed from synonymy with H. drakei Knisch.